2017
DOI: 10.1016/j.paid.2016.07.042
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety mediates the relationship between multidimensional perfectionism and insomnia disorder

Abstract: Individuals with insomnia often report aspects of perfectionism alongside symptoms of anxiety and depression. However, there has been limited examination of these factors together. The current study investigated whether individuals with insomnia report increased perfectionism compared to normal-sleepers. Further, the mediating role of anxiety and depression was examined. Participants were 39 individuals with DSM-5 defined Insomnia Disorder, and 39 normal-sleepers, who completed two measures of multidimensional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
38
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 14 publications
4
38
0
1
Order By: Relevance
“…Indeed, most studies did not use the PSQI to assess sleep. Lundh et al (1994) 19 used screening questions to assess sleep. Only Vincent and Walker (2000) 10 used the PSQI to assess sleep.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, most studies did not use the PSQI to assess sleep. Lundh et al (1994) 19 used screening questions to assess sleep. Only Vincent and Walker (2000) 10 used the PSQI to assess sleep.…”
Section: Discussionmentioning
confidence: 99%
“…between insomnia and perfectionism showed that insomnia is associated with DA, 9,19 PS, 9 CM, 9,19 and PC. 10,19 Studies reporting on the association between insomnia symptoms and perfectionism showed that insomnia symptoms are associated with DA, 16,17 PS, 16 CM, 15,16 and PC.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations